PENGARUH JUMLAH DAN JENIS DAUN SIRIH PADA SEDIAAN REBUSAN TERHADAP PERTUMBUHAN BAKTERI Aggregatibacter actinomycetemcomitans - , MONICA DWI ANGGRAINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aggregatibacter actinomycetemcomitans is one of the bacteria that cause periodontitis. The use of herbal medicine, such as red betel leaf (Piper crocatum) and yellow betel leaf (Piper betle L.), is increasing because the processing can be done easily. Red betel leaf (Piper crocatum) and yellow betel leaf (Piper betle L.) contain antibacterial compounds. The aim of study is to determine the antibacterial inhibition of Aggregatibacter actinomycetemcomitans red betel leaf (Piper crocatum) and yellow betel leaf (Piper betle L.) 30 sheets and 40 sheets in decoction. Red betel leaf (Piper crocatum) and yellow betel leaf (Piper betle L.) 30 sheets and 40 sheets processed by decoction using sterile aquades. Bacterial culture of Aggregatibacter actinomycetemcomitans was diluted with physiological saline to obtain 10 8 CFU / ml. Effect of red betel leaf (Piper crocatum) and yellow betel leaf (Piper betle L.) 30 sheet and 40 sheet decoction to the growth of Aggregatibacter actinomycetemcomitans was determined by counting the number of Aggregatibacter actinomycetemcomitans colonies on a petri dish that had been incubated for 24 hours. Aggregatibacter actinomycetemcomitans colonies were counted with colony counter. One way ANOVA test results showed that the decoction of red betel leaf (Piper crocatum) and yellow betel leaf (Piper betle L.) 30 sheets and 40 sheets give significantly effect on the growth of Aggregatibacter actinomycetemcomitans. Decoction of yellow betel leaf (Piper betle L.) 40 sheets has the highest ability to inhibit the growth of Aggregatibacter actinomycetemcomitans between the other groups.